Intermetallic growth kinetics for Sn-3.5Ag-0.1Ni solder sandwiched between two copper substrates / Wan Nur Suhaiza Sukri - Sukri, Wan Nur Suhaiza (2021)
The intermetallic growth kinetics between Cu/Sn-3.5Ag-0.1Ni/Cu interfacial reactions were studied during reflow aging at 250℃ for 1, 10, 20, 30 and 40 minutes using Cu/Sn- 3.5Ag-0.1Ni/Cu sandwich solder. A typical Sn-Cu-Ni intermetallic compound layer was formed lower and upper interfacial after reflow. A (Cu, Ni)6Sn5 intermetallic compound layer was observed at both lower and upper Cu/Sn-3.5Ag-0.1Ni/Cu interface. The classical kinetic theory may clearly explain the growth kinetics of the overall interfacial intermetallic compound layer for this study. In addition, the lower interfacial has thicker intermetallic compound and higher intermetallic growth kinetics than upper interfacial.